Comparative evaluation of mineral profiles in different blood specimens of dairy cows at different production phases - Hussein, Hussein Awad; Müller, Anja-Elivera; Staufenbiel, Rudolf (Frontiers in Veterinary Science, 2022)
Background Evaluation of mineral profiles including essential and toxic elements in dairy cows provides fundamental information for bovine practitioners during regular herd supervision and monitoring. The present research was designed to investigate the variations of mineral profiles in different blood specimens of dairy cows at different lactation stages. Methods This study was divided into two parts: the first included 32 cows, which were classified into four groups according to their lactation stages, and the second involved 10 cows at mid-lactation. The concentrations of copper (Cu), zinc (Zn), selenium (Se), manganese (Mn), barium (Ba), strontium (Sr), calcium (Ca), magnesium (Mg), total phosphorous (P), sulfur (S), cobalt (Co), silicon (Si), lithium (Li), nickel (Ni), thallium (Tl), boron (B), aluminum (Al), uranium (U), and arsenic (As) were measured in serum, ethylene diamine tetraacetic acid (EDTA) plasma, heparin plasma, and EDTA whole blood samples. Results The concentrations of Cu, Zn, Fe, Mn, Ba, and Sr showed significant variations among the dairy cows of different lactation stages (p < 0.05). Strong regressions were determined between the mineral concentrations in individual and pooled samples (R2 = 0.991, p = 0.000). In comparison to other blood sample types, the concentration of Cu, Ba, and Sr was higher in EDTA plasma (p < 0.000). In addition, the values of Zn, Se, Fe, and Mn were significantly increased in heparin and EDTA whole blood samples. Concentrations of Ca and Mg, and P were higher in EDTA plasma, and EDTA whole blood samples, respectively. Furthermore, the mean values of Si, Li, Ni, and Tl showed significant increases in EDTA plasma, while S values were higher in EDTA whole blood samples (p < 0.000). Concentrations of Al and U exhibited significant increases in serum samples (p < 0.000). Conclusion Concentrations of Cu, Zn, Fe, Mn, Ba, and Sr undergo physiological variations among dairy cows at different lactation stages. Therefore, caution should be taken during assessment of these minerals. The concentrations of essential and toxic elements, as well as Ca, P, Mg, and S, varied among the different blood sample specimens, indicating their interpretations should be based on this regard. During dairy herd supervision, the use of pool sample, instead of individual ones, for determination of mineral status may be promising to minimize the costs of individual sample measurements. In general, EDTA plasma may be more suitable for measurements of Ca, Mg, P, and S. It seems that EDTA plasma and heparinized plasma are suited for the estimation of Se and Fe, respectively.